2007
DOI: 10.1002/dmrr.751
|View full text |Cite
|
Sign up to set email alerts
|

C‐fos expression at the spinal dorsal horn of streptozotocin‐induced diabetic rats

Abstract: The present study demonstrates that the responses of spinal cord neurons are strongly affected during diabetes. The higher baseline neuronal activity probably underlies the spontaneous pain detected during diabetes since the spinal dorsal horn is the major relay station in the ascending transmission of nociceptive input to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
1
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 58 publications
9
30
1
3
Order By: Relevance
“…These results differ from those of a previous study (Morgado and Tavares, 2007), which showed that c-Fos-LI cells were present in the spinal cord from STZ-induced diabetic rats with or without innocuous or noxious stimuli. However, in agreement with previous studies (Molander et al, 1992(Molander et al, , 1994Day et al, 2001;Lue et al, 2002), c-Fos-LI cells were observed in the dorsal column nuclei (DCN) only after electrical stimulation of the injured peripheral nerve.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…These results differ from those of a previous study (Morgado and Tavares, 2007), which showed that c-Fos-LI cells were present in the spinal cord from STZ-induced diabetic rats with or without innocuous or noxious stimuli. However, in agreement with previous studies (Molander et al, 1992(Molander et al, , 1994Day et al, 2001;Lue et al, 2002), c-Fos-LI cells were observed in the dorsal column nuclei (DCN) only after electrical stimulation of the injured peripheral nerve.…”
Section: Discussioncontrasting
confidence: 85%
“…In this study, the diabetic median nerve was exposed to a lower-intensity stimulation, which was thought to excite only the large myelinated Aa/b fibers that transmit innocuous information (Woolf and Wall, 1982;Nishimori et al, 1990;Tsai et al, 2009), and resulted in the absence of c-Fos-LI cells in the CN in diabetic rats without MNT. Similarly, a previous study demonstrated that innocuous stimulation did not induce a significant increase in the number of c-Fos-LI cells in the spinal cord dorsal horn in control or diabetic rats (Morgado and Tavares, 2007). Although the functional significance of c-Fos expression in the diabetic CN after electrical stimulation to the transected median nerve is unclear, our previous study showed that the up-regulation of c-Fos expression in the CN was closely correlated with the magnitude of tactile hypersensitivity following median nerve injury, but not noxious thermal hyperalgesia .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…There is a widely held assumption that increased primary afferent sensitivity or activity is a major drive of many neuropathic pain states, including diabetes, and the ability of drugs acting adjacent to peripheral nerve terminals to rapidly alleviate mechanical hyperalgesia and tactile allodynia supports this concept [ Fos-immunoreactive neurons in the dorsal horn of the spinal cord has recently demonstrated increased basal expression in STZ-diabetic rats, which can be interpreted as a marker of increased spontaneous activity of nociceptive primary afferents, assuming that diabetes does not inherently alter local factors that modulate expression of the protein [40]. However, contradictory reports regarding altered spontaneous and evoked activity of primary afferents in STZ-diabetic rats have not entirely resolved this issue.…”
Section: Mechanismsmentioning
confidence: 92%
“…Measures of ultrasonic vocalizations in rats indicate that while vocalization patterns change in certain nerve injury models of neuropathic pain, they are not altered by diabetes [38,39]. Consequently, most recent studies have largely retained the long-established approach of measuring behavioral responses to non-noxious or noxious stimuli as surrogates for allodynia and hyperalgesia, although one interesting histologic study used spinal Fos protein expression in response to noxious stimuli as a surrogate marker of input to the spinal cord [40]. Limb withdrawal from noxious heat or cold and from light touch can be equated to similar quantitative sensory tests in human subjects and are particularly attractive for screening therapeutics because they allow the multiple measurements needed to produce time course and dose:effect profiles.…”
Section: Assaysmentioning
confidence: 98%